Self-perception of physical activity and fitness is related to lower psychosomatic health symptoms in adolescents with unhealthy lifestyles - Migle Baceviciene; Rasa Jankauskiene; Arunas Emeljanovas (BMC, 2019)
Abstract The general aim of the present study was to examine how physical activity, participation in sports, and beliefs about personal physical activity and physical fitness are associated with adolescents' psychosomatic health complaints (PHC) in relation to their lifestyles. Methods A total of 3284 11-19-year-old adolescents (average age 14.9 ± 2.0; 48.6% male) participated in the population-based cross-sectional study. Self-administered questionnaires addressed lifestyle, sports participation, physical activity, physical fitness perception, and PHC. Results Female gender (OR = 1.92; 95% CI = 1.57-2.35), smoking (OR = 1.31; 95%PI = 1.01-1.68), alcohol consumption (OR = 1.60; 95%PI = 1.30-1.97), unhealthy foods (OR = 1.14; 95%PI = 1.04-1.26), hours of internet use (OR = 1.14; 95%PI = 1.07-1.21), and poor personal fitness perception (OR = 1.60; 95% CI = 1.27-2.02) were associated with PHC in adolescents. Lower physical activity and self-perceived insufficient physical activity, perception of physical fitness as being poor, and not participating in sports were associated with greater somatic and psychological complaints controlling for age, gender, and BMI. Participation in sports and physical activity did not change PHC in adolescents involved in unhealthy behaviour. However, a positive perception of one's own physical activity and physical fitness decreased PHC in adolescents who reported an unhealthy lifestyle. Conclusions Adolescents demonstrating poorer health-related behavioural profiles showed higher PHC. Physical activity and sports participation were related to lower PHC. Positive physical activity and physical fitness perception changed the associations between PHC and unhealthy lifestyle: adolescents perceiving themselves as sufficiently physically active and those evaluating their physical fitness as good showed lower PHC, despite the presence of unhealthy habits (high screen time, drinking alcohol, smoking, and consuming unhealthy foods). It is important to study cognitive factors when exploring the associations between adolescent lifestyles and PHC. These results are important for health promotion and education programmes aimed at improving healthy lifestyle and psychosocial well-being in adolescents.